Kinerja Anak Kambing Bligon Setelah Introduksi Pejantan Unggul di Kelompok Ternak Purwo Manunggal, Gunungkidul - Tri Satya Mastuti Widi; Endang Baliarti; Febri Ariyanti; Nono Ngadiono; I Gede Suparta Budisatria; Panjono Panjono; Muhamad Danang Eko Yulianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Goats have become increasingly popular among smallholder mixed-crop-livestock farmers, such as in Gunungkidul District. Farmers in this district have good access to the market. However, farmers keep local breed,Bligon, without any improvement within breed. This study was started by introducing superior bucks to local does and aimed to evaluate the productivity of their progenies. Nineteenth kids, resulted from mating of local does andlocal bucks and 28 kids, resulted from mating of local does and superior Ettawa crossbred bucks were used in this study. Birth and weaning weights, average daily gain and body size of pre-weaning kids were measured. Birth andweaning weights of pre-weaning crossbred kids tended to be higher than local those of local kids but not significantly different. The average daily gain of crossbred kids were significantly higher than local kids. Body sizes interms of girth of chest (GC), height at the wither (HW) and length of the body (LB) of crossbreed kids were significantly higher than those of local kids. Productivity of pre-weaning kids in the preliminary phase of the introductionof superior bucks were highly varied. Continuous improvement of breeding system is then needed. Introduction of superior bucks has to be supported by good keeping management.